LANGUAGE BARRIERS IN ENGLISH LEARNING IN HIGH SCHOOL (International Seven Journal of Multidisciplinary, 2025)
English learning in high school education in Mexico faces multiple linguistic barriers that limit the development of students' communicative competencies. This quantitative, descriptive, and exploratory study identifies which language skills present the greatest difficulties for students. A Likert-type questionnaire was administered to 45 students, investigating their perceptions of listening comprehension, speaking, reading, and writing. The results show that productive skills, especially speaking, represent the greatest challenges due to factors such as lack of practice, anxiety, and limited feedback. It is concluded that more inclusive and contextualized pedagogical strategies are needed, including the use of mobile language learning applications, to promote balanced development across all four skills, with special emphasis on oral production, in order to strengthen communicative competence at this educational level.